Analisis Sinergi Eksekutif Dan Legislatif Dalam Penyusunan Peraturan Daerah Tentang APBD Di Kabupaten Kolaka Utara - Kamaludin Kamaludin; Arman; Swastiani Dunggio (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2022)
This study aims to describe the process of planning, discussing, and enacting local regulations on the Regional and Regional Budgets in North Kolaka Regency and the factors that influence them. The research method uses a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The results of the research are the planning, discussion, and stipulation process in making regional regulations in North Kolaka Regency, the executive and legislature have completed procedures on the preparation of the existing Expenditure and Regional Budgets. However, the planning process has not been optimal for regional regulations on Expenditures and Regional Budgets. This is reflected in the making of the General Budget Policy and the Priority of the Temporary Budget Ceiling. As a result, executive power is limited, such as changes in the scope of government institutions in the North Kolaka Regency which are not in accordance with the initial design. This slows down the discussion process. while the determination process must be timely. During the process, the executive and the legislature were involved, but the relationship between the two did not look good. This can be seen in the discussion process between the executive and the legislature who maintain their respective opinions which resulted in the slow submission of the Regional Revenue and Expenditure Budget Draft to the Ministry of Home Affairs. The process of planning, discussing and determining the 2020 Fiscal and Regional Budget in North Kolaka Regency is influenced by various factors, including supporting and inhibiting factors. supporting factors between legislation and good communication. while the inhibiting factor. that is. institutional changes within the government of North Kolaka Regency, understanding and participating in human resources and political interests